Etika Bisnis dalam Islam: Pedoman Sukses dengan Kejujuran dan Keadilan: Business Ethics in Islam: Guidelines for Success with Honesty and Justice - Gea Dwiki Yustanto; Anas Vhio Sadewa; Andri Eka Saputra; Alvira Choirunissa Putri; Savna Cindy Claudia; Aditya Candra; Ahmad Nurrohim (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
In Islam, business ethics is an important foundation for every individual involved in the business world. Islamic principles emphasize the importance of running a business with honesty, fairness and integrity, which are the keys to achieving success that is not only material but also spiritual. This research aims to identify and analyze the implementation of Islamic business ethics in Islamic business practices and reveal its impact on business success and blessings. The type of research used is qualitative research with a descriptive analysis approach. The research results show that businesses can develop and gain benefits by implementing these values. In addition, the application of this ethics creates healthy, mutually beneficial and socially responsible business relationships.